MENGHITUNG RENDEMEN BIODIESEL DARI MINYAK JELANTAH HASIL PENGGORENGAN ABON CAKALANG - Alfin Mario Momongan; Daniel P.M. Ludong; Freeke Pangkerego (COCOS, 2017)
ABSTRACTCooked oil is a type of oil obained from frying remains of various household consumption. This oil contains free fatty acids produced by the reaction of oxdation and hydrolisis during frying, so that this oil is a house hold waste. UD. Trikora is a company that produced skipjack shredded meat and uses cooking oil for frying. The utilization of this cooked oil is an alternative problem solving of waste oil disposal and public health. The survey result indicated that this cooked oil was placed in the gallons and some of them was taken by the employers. Processing of this cooked oil into biodiesel as an alternative fuel diesel engine, is an altenative problem solving. Based on these reasons, a descriptive study was conducted to evaluate the biodiesel rendement of this cooking oil. The result showed that 78,8 % biodiesel was obtained from transesterification reaction of 500 mL cooked oil using 2 g NaOH and 100 mL ethanol as solvent.Keywords :Rendement, Wrapping oil, Transesterification